Leia, Princess of Alderaan - Gray, Claudia (2017)
The story of how Leia Organa comes to join the Rebellion. Sixteen-year-old Princess Leia has been taking rigorous survival courses, practicing politics, and spearheading relief missions to worlds under Imperial control so that she becomes formally named heir to the throne of Alderaan. When her parents begin acting strange, sixteen-year-old Princes Leia sets out to uncover their secrets, putting her in the path of the watchful Empire. She finds herself facing the choice of dedicating herself to the people of Alderaan, including the man she loves, or to the galaxy at large which is in desperate need of a rebel hero.
"Journey to Star Wars: The Last Jedi"--Cover.
"Set before Star wars: a new hope and contains clues about the upcoming film Star wars: the last Jedi!"--Back cover.
Accelerated Reader AR
Keywords: Organa, Leia -- (Fictitious character) -- Juvenile fiction; Organa, Leia -- (Fictitious character); Organa, Leia -- (Fictitious character) -- Fiction; Government, Resistance to -- Fiction; Space warfare -- Fiction; Princesses -- Fiction; Star Wars fiction; Space warfare -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Science fiction; Government, Resistance to -- Fiction; Space warfare -- Fiction; JUVENILE FICTION -- Action & Adventure; JUVENILE FICTION -- Fantasy & Magic; JUVENILE FICTION -- Media Tie-In.; Government, Resistance to; Princesses; Science fiction; Space warfare; Star Wars fiction; Resistance to government -- Fiction; Space warfare -- Fiction; Princesses -- Fiction; Star Wars fiction -- Fiction; Young adult fiction; Young adult fiction; Fiction; Juvenile works; Science fiction; Young adult works; Science fiction; Science fiction